GEOGRAPHIC INFORMATION SYSTEM PEMETAAN TRAYEK BUS SEKOLAH DAN HALTE DI CENTRAL BUSINESS DISTRICT (CBD) BANGKINANG - Nurul Ismah; Novi Yona Sidratul Munti; Hanantatur Adeswastoto (Universitas Pahlawan Tuanku Tambusai, 2021)
Along with the development of increasingly advanced technology, the working world is required to improve it performance One of the jobs that really supports the development in Bangkinang is facilitating students and educators with the transportation bus or school bus. This bus is usually used to transport students and educators to and from school. This bus always operates in according with the routes. however, the lack of information obtained by the community causes many educator and students not to optimize the facilities provided by the Kampar Regency Transportation Office. To support this, a geographic information system is used tu map school bus routes and these stops and use Google Maps to display the map. Based on that, hoped that the research objectives can be achieved, to helping the community and students in obtaining information about school buses, knowing the routes of each school bus, knowing the location of the bus stop, and hope that the community optimizes existing facilities such as bus stops.he designed system is a web-based system as a medium to provide information to the public. The programming languages used are HTML, PHP, and Mysql as databases which are expected to facilitate admins in managing data efficiently and easier for users to access this School Bus Route and Bus Stop Mapping information system.